Effects of physical activity on cognitive function among patients with diabetes in China: a nationally longitudinal study - Anying Bai; Liyuan Tao; Jia Huang; Jing Tao; Jue Liu (BMC, 2021)
Abstract Background We aimed to examine the effect of physical activity on different cognitive domains among patients with diabetes. Methods We used two waves of data from the Chinese Health and Retirement Longitudinal Study (CHARLS, 2013-2015), a nationally representative dataset of Chinese population aged over 45. Total physical activity scores were calculated based on the International Physical Activity Questionnaire (IPAQ). Executive function and episodic memory were used as measures of cognitive function. We conducted lagged dependent variable models to explore the association between physical activity and cognitive function in full sample as well as two different age groups (45-65, ≥65). Results: 862 diabetic patients were included. We found that diabetic participants who had greater level of physical activity at baseline were associated with better episodic memory function in 2 years (p < 0.05). Moreover, physical activity was significantly associated with less decline in episodic memory in fully adjusted models, and the associations were stronger among patients aged 45-65 years (p < 0.05). No statistically significant association was found between physical activity and executive function in all age groups. Conclusions Physical activity may prevent some of the potential decline in episodic memory in diabetic patients. Clinicians and public health departments should strengthen the promotion of physical activity and develop early screening tools among diabetic participants to prevent the progression of cognitive impairment.